Answer:
(4,5)
Step-by-step explanation:
Given the system of equations:
![\begin{gathered} y=2x-3 \\ y=-x+9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/q4m7s3b0u0grefyy0bfb5ooczvku4oyupt.png)
We graph each of the equation using the x and y-intercepts.
First Equation(y=2x-3)
When x=0
![\begin{gathered} y=2x-3 \\ y=2(0)-3 \\ y=-3 \\ \implies(0,-3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1vd0kc5qa1fmzj42wiyf0gjacwza4kfijm.png)
When y=0
![\begin{gathered} 0=2x-3 \\ 2x=3 \\ x=(3)/(2) \\ x=1.5 \\ \implies(1.5,0) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/azdgyo7s86rbe6v3liygz06g7px55u99eo.png)
Next, join the points (0,-3) and (1.5,0) as shown below:
Second Equation(y=-x+9)
When x=0
![\begin{gathered} y=-x+9 \\ y=-0+9 \\ y=9 \\ \implies(0,9) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qz31o38oe5rrpxgqcs2xhakov97u6aawdt.png)
When y=0
![\begin{gathered} 0=-x+9 \\ x=9 \\ \implies(9,0) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rip17h9zralrwxpa109hakmlzx03gdndxx.png)
Next, join the points (0,9) and (9,0) on the same graph as shown below:
The point where the two lines intersect is the solution to the system of equations.
Therefore, the solution is (4,5).